1999
DOI: 10.1161/01.hyp.33.1.591
|View full text |Cite
|
Sign up to set email alerts
|

Daily Aerobic Exercise Improves Reactive Hyperemia in Patients With Essential Hypertension

Abstract: The effects of long-term aerobic exercise on endothelial function in patients with essential hypertension remain unclear. To determine whether endothelial function relating to forearm hemodynamics in these patients differs from normotensive subjects and whether endothelial function can be modified by continued physical exercise, we randomized patients with essential hypertension into a group that engaged in 30 minutes of brisk walking 5 to 7 times weekly for 12 weeks (n20) or a group that underwent no activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(118 citation statements)
references
References 40 publications
4
108
1
5
Order By: Relevance
“…For example, Hagberg et al 32 found that regular exercise has the ability to reduce BP in approximately 75.0% of hypertensive patients and that training with moderate intensity seems to generate greater benefits than with high intensity, for such reductions. Higashi et al 4 observed a beneficial effect of regular aerobic exercise on blood pressure values for hypertensive patients.…”
Section: Figure 2 -Blood Flow (Panel a And B) And Vascular Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…For example, Hagberg et al 32 found that regular exercise has the ability to reduce BP in approximately 75.0% of hypertensive patients and that training with moderate intensity seems to generate greater benefits than with high intensity, for such reductions. Higashi et al 4 observed a beneficial effect of regular aerobic exercise on blood pressure values for hypertensive patients.…”
Section: Figure 2 -Blood Flow (Panel a And B) And Vascular Resistancementioning
confidence: 99%
“…The release of NO has been considered as a strong mediator for reactive hyperemia in peripheral arteries 4 . Thus, low levels of NOx observed in the TC + CC group, associated with the responses of BF among groups in the pre-training evaluation, are in agreement with other studies that have shown similar results 24 .…”
Section: Figure 2 -Blood Flow (Panel a And B) And Vascular Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…10 More recently, it has been suggested that improvement of endothelial function contributes to the reduction of blood pressure after training. [12][13][14] It is likely that the lowering of blood pressure by training is multifactorial and further studies are needed to elucidate the mechanisms. 9 Physical training, diet and blood pressure control…”
Section: Basic Mechanismsmentioning
confidence: 99%
“…Reduction of insulin resistance and improvement in endothelial function may also contribute. [19,20] Importantly, this reduction appeared to be independent of the intensity, frequency and type of exercise program. BP reduction was seen in normotensives also and was not inß uenced by initial weight.…”
Section: Increased Physical Activitymentioning
confidence: 93%